2020
DOI: 10.1002/mds3.10114
|View full text |Cite
|
Sign up to set email alerts
|

Setting behaviour, mechanical properties and heat generation under alternate current magnetic fields of Fe3O4/TiO2/PMMA composite bone cement

Abstract: Poly(methyl methacrylate) (PMMA) bone cements have been used as fillers for bone defects because of their excellent mechanical properties and injectability. PMMA bone cements containing magnetite (Fe 3 O 4) particles have been studied for application in magnetic hyperthermia treatment of metastatic bone tumours (Bruno et al.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In this study, two cement samples of F25T15-3/2-42 and F30T15-3/2-42 were subjected to SEM and TF-XRD analyses as shown in Figure 2, since we confirmed that these samples show both heat-generating ability and apatiteforming ability in our previous studies. 25,26 The surface morphology of the samples was very similar when observed using SEM, as shown in Figure 2(a). The TF-XRD peaks ascribed to TiO 2 (rutile and anatase) and Fe 3 O 4 (magnetite) were clearly observed for cement samples F25T15-3/2-42 and F30T15-3/2-42 (Figure 2(b)), and they were almost identical to powder XRD peaks of original Fe 3 O 4 and TiO 2 powders.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…In this study, two cement samples of F25T15-3/2-42 and F30T15-3/2-42 were subjected to SEM and TF-XRD analyses as shown in Figure 2, since we confirmed that these samples show both heat-generating ability and apatiteforming ability in our previous studies. 25,26 The surface morphology of the samples was very similar when observed using SEM, as shown in Figure 2(a). The TF-XRD peaks ascribed to TiO 2 (rutile and anatase) and Fe 3 O 4 (magnetite) were clearly observed for cement samples F25T15-3/2-42 and F30T15-3/2-42 (Figure 2(b)), and they were almost identical to powder XRD peaks of original Fe 3 O 4 and TiO 2 powders.…”
Section: Resultsmentioning
confidence: 61%
“…The TF-XRD peaks ascribed to TiO 2 (rutile and anatase) and Fe 3 O 4 (magnetite) were clearly observed for cement samples F25T15-3/2-42 and F30T15-3/2-42 (Figure 2(b)), and they were almost identical to powder XRD peaks of original Fe 3 O 4 and TiO 2 powders. 25 According to the total DNA levels isolated from MC3T3-E1 cells adherent to F0T0-3/2-42, F25T15-3/2-42, and F30T15-3/2-42 in Figure 3, MC3T3-E1 cells proliferated gradually up to 7 days on all samples; however, cell proliferation was significantly suppressed for F25T15-3/2-42 and F30T15-3/2-42 cultured for 5 days compared to F0T0-3/2-42. Further, suppression was observed for F25T15-3/ 2-42 cultured for 7 days compared to the control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations